Etika Keuangan Hamba Tuhan: Kajian Eksegetikal Terhadap 1 Timotius 6:3-10 - Bakhoh Jatmiko; Desi Erlina Zega (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
The background of this article was the financial problems that occurred in the context of a clergy's life and ministries institution. There were court cases of clergies and church organizations due to legal disputes and asset issues. This article aimed to get ethical principles from biblical research according to the minister's life and how they related to money matters. The research question tried to answer was, what are the economic ethics principles for the ministers based on 1 Timothy 6:3-10? Method applied in this research was qualitative descriptive with a literature study approach. The authors used the exegetical method for some keywords in the focused text to elaborate and explain the text. The finance ethical principles for the ministers found are: not making a material gain as a purpose of the ministries, living with contentment, developing self-control, warding off materialism.